Pengembangan Strategi Pemasaran Pada Jaringan Bisnis Nasi Gigit Candu - Resya Dwi Marselina; Nida Fadhillah Salsabila; Rindiawati Gustiara; Ira Nurhafifah; Maulani Lestari; Rima Dinwiati Hamidah (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
This research is motivated by business networks to expand professional networks, create opportunities and businesses or jobs. Achieving professional success relies heavily on having a network of quality contacts. Therefore, networking is key in work life. Breakfast in the morning has become a culture for Indonesian people. The breakfast culture has become an activity as evidenced by the diversity of sellers offering various types of food suitable for breakfast. Breakfast is an activity of eating and drinking between morning and 9 o'clock to meet nutritional needs. Based on the above, easy and practical rice innovation is needed. To respond to this, the author conducted marketing development strategy research on business networks carried out by the UMKM Nasi Gigit Candu. The aim of this research is to find out the marketing development strategy for the Nasi Gigit Candu business network. This research was conducted directly with the owner of Nasi Gigit Opium. This research looks for how the development of business network marketing is carried out by entrepreneurs of the Nasi Gigit Opium Business to decide on product marketing development starting from making breakfast products to products that are marketed into the hands of consumers. This research uses qualitative and quantitative methods, namely by direct interviews with Nasi Gigit Opdu MSME owners and financial management.